2007
DOI: 10.1185/030079907x178874
|View full text |Cite
|
Sign up to set email alerts
|

A 2-night, 3-period, crossover study of ramelteon's efficacy and safety in older adults with chronic insomnia

Abstract: In older adults with chronic primary insomnia, ramelteon produced significant reductions in latency to persistent sleep and increases in total sleep time and sleep efficacy, and showed no evidence of adverse next-day psychomotor or cognitive effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
87
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 111 publications
(91 citation statements)
references
References 32 publications
3
87
1
Order By: Relevance
“…[118][119][120][121] The overall quality of evidence from these studies was downgraded to very low due to substantial heterogeneity across studies, imprecision and potential publication bias. The overall evidence for ramelteon 8 mg. was weakly in favor of its effectiveness for the treatment of sleep onset disturbance only.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[118][119][120][121] The overall quality of evidence from these studies was downgraded to very low due to substantial heterogeneity across studies, imprecision and potential publication bias. The overall evidence for ramelteon 8 mg. was weakly in favor of its effectiveness for the treatment of sleep onset disturbance only.…”
Section: Discussionmentioning
confidence: 99%
“…[118][119][120][121] Subjects in all studies demonstrated chronic primary insomnia with associated daytime complaints. All studies required mean objective LPS of > 20 min on two nights of PSG screening.…”
Section: Discussionmentioning
confidence: 99%
“…This indication is supported by self-report and polysomnographic studies showing that sleep onset is hastened along in a dosage range of 4 to 32 mg [59][60][61][62][63][64], although the indicated clinical dose is 8 mg. The incidence or insomnia increases in the elderly, and studies of remelteon have been conducted in elderly primary insomniacs, which show its efficacy in this population [60,61]. Tolerance to sleep onset-inducing effects did not develop in the 6-to 12-month studies that have been conducted [63,64].…”
Section: Efficacymentioning
confidence: 90%
“…The efficacy and safety of ramelteon in treating insomnia have been proven in a number of clinical studies conducted on elderly insomniacs [Richardson et al 2009;Roth et al 2007;Zammit et al 2007;Erman et al 2006]. Ramelteon may have considerable therapeutic potential in treating the sleep problems including RBD seen in PD.…”
Section: Melatonin As a Therapeutic Agent In Parkinson's Diseasementioning
confidence: 99%